The examination of the effect of carrier waveform variations on output voltage of multilevel inverters - Tuncer, Servet (My University, 2009)
In this paper, the effect of carrier waveform variations on inverter output voltage in multilevel inverters is examined. For this aim, carrier waveforms with various frequency and amplitude are constructed and compared with the reference sinusoidal signals. The obtained PWM waveforms are then applied to the power switches of the inverter. A five-level inverter prototype implemented and the real-time signals are produced using dSPACE DS1103 controller board and software's. The proposed multilevel sinusoidal PWM (SPWM) strategy is tested experimentally and the results obtained are presented.
Çok sevi?yeli? evi?ri?ci?lerde taşiyici dalga şekli? de?i?şi?mleri?ni?n çikiş geri?li?mi? üzeri?ne etki?leri?ni?n i?ncelenmesi?
Keywords: DS1103 controller board; Multilevel inverter; Sinusoidal PWM technique